2014
DOI: 10.1002/jor.22628
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing bone formation in posterior spine fusion using rhBMP‐2 and zoledronic acid in wild type and NF1 deficient mice

Abstract: Spinal pseudarthrosis is a well described complication of spine fusion surgery in NF1 patients. Reduced bone formation and excessive resorption have been described in NF1 and anti-resorptive agents may be advantageous in these individuals. In this study, 16 wild type and 16 Nf1 þ/À mice were subjected to posterolateral fusion using collagen sponges containing 5 mg rhBMP-2 introduced bilaterally. Mice were dosed twice weekly with 0.02 mg/kg zoledronic acid (ZA) or sterile saline. The fusion mass was assessed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Recently, in vitro and in vivo attempts to influence osteoblasts of patients with NF1 using bisphosphonates have yielded contradictory results for the suitability of this group of compounds for the treatment of NF1-associated osteoporosis (59)(60)(61)(62). The patient presented here had not been medicated with bisphosphonates, therefore the effect of this group of substances has only theoretical significance with respect to the pathogenesis of bone disintegration in NF1 in the presented case.…”
Section: Giant Cell Granuloma (Gcg) Of Mandible In Nf1mentioning
confidence: 84%
“…Recently, in vitro and in vivo attempts to influence osteoblasts of patients with NF1 using bisphosphonates have yielded contradictory results for the suitability of this group of compounds for the treatment of NF1-associated osteoporosis (59)(60)(61)(62). The patient presented here had not been medicated with bisphosphonates, therefore the effect of this group of substances has only theoretical significance with respect to the pathogenesis of bone disintegration in NF1 in the presented case.…”
Section: Giant Cell Granuloma (Gcg) Of Mandible In Nf1mentioning
confidence: 84%
“…Our posterolateral model is distinguished from previous models in its use of a fusion bed encompassing both the facets and the transverse processes, which increases the total surface area available for fusion, thereby improving the fusion rate. Although a prior mouse model using only intertransverse fusion had a fusion rate of 62.5%, the combination of decortication with autograft was not reported; likewise, most models in the literature have reported decortication alone or adjunct supplementation [11][12][13]15,[18][19][20][21] . The fusion rate in the present study is also greater than the 67% fusion rate observed in a rabbit posterolateral model, indicating that our mouse model is optimized to study fusion biology whereas the rabbit model is better optimized to study differences between fusion adjuncts 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach did not diminish accumulation of fibrotic tissue within the callus. Another approach tested in a posterolateral fusion model of lumbar spine the combination of BMP-2 and zoledronic acid [48]. This Citation: Seifert W, Kolanczyk M, Kühnisch J (2016) The Skeletal Phenotype in Neurofibromatosis Type 1 -Structural Defects, Molecular Mechanisms and Therapeutic Approaches.…”
Section: Therapeutic Approaches Targeting Fracture Healing In Micementioning
confidence: 99%